2016
DOI: 10.1175/jas-d-15-0072.1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Quasi-Biennial Oscillation and Sea Surface Temperature Variability on Downward Wave Coupling in the Northern Hemisphere

Abstract: Downward wave coupling occurs when an upward-propagating planetary wave from the troposphere decelerates the flow in the upper stratosphere and forms a downward reflecting surface that redirects waves back to the troposphere. To test this mechanism and potential factors influencing the downward wave coupling, three 145-yr sensitivity simulations with NCAR's Community Earth System Model [CESM1(WACCM)], a state-of-the-art high-top chemistry-climate model, are analyzed. The results show that the quasi-biennial os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 73 publications
2
33
1
1
Order By: Relevance
“…These strong vortex anomalies during this period are in turn consistent with the significant increase (decrease) of 1‐hPa (10‐hPa) first SFWs in the FixedSST experiment. Note that the stronger and hence less disturbed polar vortex in the FixedSST experiment is consistent with missing variability sources in the troposphere, which results in reduced upward wave propagation and decreased wave dissipation/breaking in the stratosphere (see Figure S1 in Lubis, Matthes, et al, ).…”
Section: Influence Of Remote Variability Sources On Sfwssupporting
confidence: 53%
See 1 more Smart Citation
“…These strong vortex anomalies during this period are in turn consistent with the significant increase (decrease) of 1‐hPa (10‐hPa) first SFWs in the FixedSST experiment. Note that the stronger and hence less disturbed polar vortex in the FixedSST experiment is consistent with missing variability sources in the troposphere, which results in reduced upward wave propagation and decreased wave dissipation/breaking in the stratosphere (see Figure S1 in Lubis, Matthes, et al, ).…”
Section: Influence Of Remote Variability Sources On Sfwssupporting
confidence: 53%
“…Figure b shows the seasonal distribution of SSWs for the four different experiments. Overall, removing the QBO leads to a substantial increase of SSW frequency (6.2 SSWs/decade in the NoQBO experiment compared to 4.1 SSWs/decade in the Natural experiment), while removing the inter‐annual SST variability leads to a decrease of SSWs frequency (2.8 SSWs/decade in the FixedSST experiment) as noticed by Lubis, Matthes, et al (). The most pronounced differences in SSW frequency between the experiments are found in December, January, and February (DJF), which correspond to the months when SSW have a prominent impact on the type of SFWs (Figure c).…”
Section: Influence Of Remote Variability Sources On Sfwsmentioning
confidence: 52%
“…Upward wave propagation is therefore explored in the wave geometry diagnostic developed in Harnik (2001) in order to understand if a preference for upward propagation by waves with an eastward phase speed can indeed be found. For further details on the diagnostic see the supporting information and Harnik (2001), Harnik and Lindzen (2001), and Lubis et al (2016).…”
Section: Wave Propagation Analysis In Two Dimensionsmentioning
confidence: 99%
“…It is well established that planetary waves play an important role in shaping the ozone hole through their impact on the polar vortex and residual circulation (e.g., Solomon, 1999;Fusco and Salby, 1999;Randel et al, 2002;Lubis et al, 2016b). Randel et al (2002) showed that variations in planetary wave forcing in the lower stratosphere during winter-spring exhibit a strong correlation with column ozone, via the following mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Appendix B: Residual-mean circulation and wave geometry diagnostics Understanding how circulation is controlled by planetary waves is the key to connecting the wave driving to polar temperatures and transport of trace gases such as ozone. The transformed Eulerian mean formulation (Andrews et al, 1987) can be used to directly examine wave effects on the circulation and ozone transport to the polar vortex (Fusco and Salby, 1999;Plumb, 2002;Lubis et al, 2016b). The residual mean circulation is calculated from the stream function ( ) of the residual TEM meridional v * and vertical w * winds as follows:…”
mentioning
confidence: 99%